The Holy Grail: highlighting the need for equitable access to dementia treatments and clinical trials - Rebekah M. Ahmed; Olivier Piguet; Catherine J. Mummery; Sharon L. Naismith; Muireann Irish (The Lancet Regional Health. Western Pacific, 2025)
Summary: In the last 5 years significant progress has been made in potential dementia treatments, yet many of these treatments come with significant burdens on the healthcare system that may limit access to treatment and care for patients. Often patients in remote and rural regions and those in low income regions are disadvantaged. Many clinical trials for dementia patients are biased to recruiting a homogenous group of patients that does not represent cultural and linguistic diversity, meaning the generalisability of trials is limited. This viewpoint discusses the barriers to access to early treatments and clinical trials for patients with dementia and offers a potential framework to address these including provision of infrastructure, regulatory change and patient education.